Nutritional status and dietary habits in preschool-age children - Lourenço, Margarida (2021)
Context: The prevalence of childhood obesity continues to increase worldwide. Its consequences are dramatic, and are associated with a higher probability of premature death and disability in adult life. This situation is so alarming that it is considered one of the greatest health challenges in the 21st century. Goals: To classify the nutritional status of preschool-age children attending selected kindergartens; To characterize the dietary habits of preschool-age children attending selected kindergartens. Methods: A non-experimental, descriptive and cross-sectional study developed in a health care centre of the Municipality of Sintra, within the scope of the School Health Programme. The sample consisted of 300 children. Results: 154 children were male, 146 were female; 140 children were 3 years old and 160 were 4 years old; 92 Children (30.6%) were overweight. Of these, 41 children were pre-obese (13.6%) and 51 were obese (17%). The most consumed foods belonged to the “meat, fish and eggs” food group. Conclusions: The prevalence of overweight children in the study sample was high. An imbalance was observed in the representation of the consumed products, due to an excessive consumption of products from the “meat, fish and eggs” food group.